Analisis Penggunaan Media Pembelajaran Braille Book KARTUNE sebagai Upaya Peningkatan Kepekaan Estetis Disabilitas Tunanetra - Adinda Kadwi L.P; Salha Hamidah; Ely Fiatus S.; Icha Silfia; Lutfi Mahmudah; Nur Fajrie (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
One of the physical limitations that attracts attention is blindness. In Indonesia, someone who experiences visual impairments is known as a blind person. This research focuses on PPSDSN Pendowo Kudus which is a Social Service Home for the Visually Sensory Disabled. Based on observations and interviews conducted by researchers regarding empowerment activities in the form of guidance at PPSDSN (Social Service Center for Visual Sensory Disabilities) Pendowo Kudus, data was obtained that the musical arts skills at PPSDSN Pendowo Kudus in their implementation experienced several obstacles including difficulties in memorizing the material and the unavailability of tutors since the start of the pandemic in 2019. Judging from the description that has been presented, the author attempts to provide a solution to this problem by proposing an idea for writing an article entitled "Analysis of the Use of Cartoon Braille Book Learning Media as an Effort to Increase the Aesthetic Sensitivity of the Blind". Through this research, it is hoped that people with visual impairments will find it easier to learn musical instrument. In this results and discussion section, the research team describes (1) How Efforts to Increase Aesthetic Sensitivity for Disabilities in general are linked to research at PPSDSN Pendowo Kudus, (2) What is the impact of using Braille Book Media, and (3) How is Braille Book Learning Media CARTOON. Braille Book KARTUNE is a learning media in the form of a book that contains musical notations for musical numbers printed in Braille and equipped with a barcode. The existence of the KARTUNE Braille Book Learning Media makes the musical team receiving benefits at PPSDSN Pendowo Kudus find it easier and more practical to learn musical notation for musical numbers.